Key lifestyles and health outcomes across 16 prevalent chronic diseases: a network analysis of an international observational study - Li, Jiaying; Fong, Daniel Yee Tak; Lok, Kris Yuet Wan; Wong, Janet Yuen Ha; Ho, Mandy Man; Choi, Edmond Pui Hang; Pandian, Vinciya; Davidson, Patricia M; Duan, Wenjie; Tarrant, Marie; Lee, Jung Jae; Lin, Chia-Chin; et al. (International Society of Global Health (ISoGH), 2024)
Background: Central and bridge nodes can drive significant overall improvements within their respective networks. We aimed to identify them in 16 prevalent chronic diseases during the coronavirus disease 2019 (COVID-19) pandemic to guide effective intervention strategies and appropriate resource allocation for most significant holistic lifestyle and health improvements.